2018
DOI: 10.1038/s41586-018-0004-7
|View full text |Cite
|
Sign up to set email alerts
|

Distributed hepatocytes expressing telomerase repopulate the liver in homeostasis and injury

Abstract: Hepatocytes are replenished gradually during homeostasis and robustly after liver injury1,2. In adults, new hepatocytes originate from the existing hepatocyte pool3-8, but the cellular source of renewing hepatocytes remains incompletely understood. Telomerase is expressed in many stem cell populations, and telomerase pathway gene mutations are linked to liver diseases9-11. Here, we identify a subset of hepatocytes that expresses high levels of telomerase and show that this hepatocyte subset repopulates the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
213
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(232 citation statements)
references
References 39 publications
9
213
0
2
Order By: Relevance
“…[ 52 ] Lin et al have shown that a subset of hepatocytes expressed high levels of telomerase and are expressed in many stem cell populations, which aids in the repopulation of liver cells during hemostasis and injury. [ 53 ] Huch et al have reported that LGR5+ adult bile duct‐derived biopotent progenitor cells from human liver can be converted into functional hepatocytes in vitro and upon transplantation in vivo. [ 52 ] Further, liver organoid technology is strongly dependent upon endogenous cell organization, self‐assembly or self‐organization, with xenogeneic components, such as Matrigel.…”
Section: Resultsmentioning
confidence: 99%
“…[ 52 ] Lin et al have shown that a subset of hepatocytes expressed high levels of telomerase and are expressed in many stem cell populations, which aids in the repopulation of liver cells during hemostasis and injury. [ 53 ] Huch et al have reported that LGR5+ adult bile duct‐derived biopotent progenitor cells from human liver can be converted into functional hepatocytes in vitro and upon transplantation in vivo. [ 52 ] Further, liver organoid technology is strongly dependent upon endogenous cell organization, self‐assembly or self‐organization, with xenogeneic components, such as Matrigel.…”
Section: Resultsmentioning
confidence: 99%
“…We used qRT–PCR to examine the levels of mRNAs encoding proteins involved in liver proliferation and found an increase in mRNAs encoding β‐catenin ( Ctnnb1 ) and GSK3β ( Gsk3b ) (Fig E). Unlike most cells in adult organs, a sub‐population of liver cells expresses Tert , which encodes the catalytic subunit of telomerase, and these cells are responsible for liver maintenance and renewal (Lin et al , ). We found that Tert abundance was significantly increased in the 30‐week‐old Mrps12 ep / ep liver (Fig E), providing an explanation for the increased cellular proliferation we observed in these mice.…”
Section: Resultsmentioning
confidence: 99%
“…They divide under the influence of WNT/RSPO3 signals secreted by CV endothelial cells (Wang et al, 2015). Separately, rare Telomerase-expressing hepatocytes scattered throughout the liver lobule also proliferate and generate small clones after long-term lineage tracing (Lin et al, 2018). However, taken as a whole, hepatocytes generally renew themselves slowly by comparison to fast-cycling tissues such as the small intestines, which renews itself every 3-5 days (Clevers et al., 2014).…”
Section: Introductionmentioning
confidence: 99%